Laparoscopic hysterectomy versus abdominal hysterectomy for severe pelvic endometriosis - Chalermchockchareonkit, Amphan; Tekasakul, Putthawan; Chaisilwattana, Pongsakdi; Sirimai, Korakot; Abd. Wahab, Noraziana (Elsevier BV, 2012)
To compare the surgical outcomes of laparoscopic hysterectomy (LH) versus abdominal hysterectomy (AH) in patients with severe pelvic endometriosis. Methods: A retrospective review of patients undergoing hysterectomy for endometriosis was conducted between January 2002 and December 2007. A total of 503 patients had severe pelvic endometriosis; of these, 115 patients underwent LH and 388 patients underwent AH. Surgical outcomes—including operative time, blood loss, length of hospital stay, and need for blood transfusion—were analyzed and compared between the 2 treatment groups. Results: Operative time was significantly longer for LH than for AH (185.1±48.7 minutes and 139.9±52.4 minutes, respectively; Pb0.001). However, estimated volume of blood loss, length of hospital stay, and complication rates were significantly less for patients in the LH group than for those in the AH group (302.6±255.1 mL versus 760.9±633.2 mL [Pb0.001]; 3.5±1.1 days versus 6.4±3.0 days [Pb0.001]; and 18.3% versus 49.0% [Pb0.001], respectively). Conclusion: Compared with AH, LH was associated with fewer complications. LH should, therefore, be the preferred surgical option for women with severe pelvic endometriosis who require a hysterectomy.